Subepithelial white deposition in the cornea associated with silicone oil and surgical management: a case report - Shao, Yuting; Liu, Xin; Shu, Yiyang; Lv, Xiao; Bi, Yanlong (Frontiers in Medicine, 2023)
A 36-year-old patient presented with a complaint of an extensive “white scar” in his right eye without pain after silicone oil left in the vitreous cavity for 12 years. Slit-lamp microscopy revealed extensive corneal leukoplakia and mild limbus neovascularization. Anterior segment optical coherence tomography revealed marked eccentric thickening of the subepithelium and normal thickness of the stroma. We proceeded with silicone oil removal and intraocular and anterior chamber lavage at first, followed by epithelial lesion excision combined with amniotic membrane transplantation three months later. The patient was satisfied with the clear cornea appearance.